Features of Islamic Children’s Books in English: A Case Study of Books Published in Malaysia - Nor, Mohd Roslan Mohd; Zainal Abidin, Ummu Zainab Al-Abidah; Nasaruddin, Nusaibah (Springer Verlag, 2018)
The purpose of this study is to investigate the elements of Islamic children’s books that are written in English by focusing on books that are available in the Malaysian market and published in Malaysia. This study applies the content analysis method, by examining the selected books of their subject matter as well as the language. The results of the study reveal that Islamic books written for children in English are distinctive in terms of the content and language features.